Konstruksi Pasangan Calon Dalam Pilgub Jateng 2008 oleh Media Massa (Kasus Pemberitaan Jawa Pos Radar Semarang dan Suara Merdeka) - Yustitia, Senja (Jurnal The Messenger, 2009)
The research samples are news about the candidates in Jawa Pos Radar Semarang and Suara Merdeka daily newspaper page one and special rubric on March 26 - June 22, 2008. The result of this research shows that Jawa Pos Radar Semarang tried to be responsive with political issues and give favorable constructs to Agus Soeyitno-Kholiq Arif, Bibit Waluyo-Rustriningsih dan HM.Tamzil-Rozaq Rais. On the other hand, they give unfavorable constructs to Bambang Sadono-M. Adnan and Sukawi Sutarip-Sudharto. Suara Merdeka give favorable constructs to Bambang Sadono-M. Adnan; Bibit Waluyo-Rustriningsibd and HM. Tamzil-Rozaq Rais but give unfavorable constructs to Agus Soeyitno-Kholiq Arif and SukawiSutarip-Sudharto.